IMPLEMENTASI PERLINDUNGAN HAK PEREMPUAN DAN STATUS HUKUM ANAK DALAM PERKARA PERCERAIAN AKIBAT KEKERASAN DALAM RUMAH TANGGA DI INDONESIA - Akmalia Salsabila; Sidi Ahyar Wiraguna (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Domestic violence (KDRT) is a leading cause of divorce initiated by women in Indonesia. This study analyzes how Indonesia’s legal system protects the rights of female victims during divorce proceedings and examines the legal consequences for children born from such marriages. Using a normative juridical approach and case studies from South Jakarta and Bandung Regency (2023–2025), the research reveals that despite strong legal frameworks—particularly Law No. 23/2004 on the Elimination of Domestic Violence and Law No. 1/1974 on Marriage—implementation remains weak due to limited legal aid access, bureaucratic court procedures, and entrenched patriarchal norms. Children from these dissolved marriages often face uncertainty regarding custody, maintenance, and inheritance rights, especially when fathers deny post-divorce responsibilities. Bandung Religious Court Decision No. 102/Pdt.G/2024/PA.Bdg exemplifies this gap, where child support was awarded but never enforced. The study concludes that procedural reform in religious courts, integrated one-stop services for victims, and stronger state accountability are essential to uphold the best interests of the child. Without systemic intervention, divorce due to domestic violence risks becoming a new form of structural violence against women and children.